2018
DOI: 10.1111/raq.12281
|View full text |Cite
|
Sign up to set email alerts
|

Insect meals in fish nutrition

Abstract: Different studies have shown that insect meals can partially or completely replace the fish and soya bean meals that are commonly used in aquaculture. However, information is lacking on the amino acid and fatty acid contents and digestibility of different insect meals. Moreover, we evaluated different proportions of insect diets and determined how these affected the nutritional values of insect meals. Our purpose was to clarify these aspects and consider the availability of protein, amino acids, lipids and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
229
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(235 citation statements)
references
References 141 publications
(129 reference statements)
5
229
0
1
Order By: Relevance
“…Insects have been proposed as an efficient and high-quality alternative protein source for poultry [ 37 , 38 ], swine [ 11 , 39 ] and carnivorous fish [ 13 , 15 , 16 , 17 , 20 , 40 ] and interest in use of insect meals in perch diets is high. Insects are a viable source of protein and lipids [ 9 , 10 ] and a typical component of Eurasian perch natural diet. Nogales-Mérida [ 9 ], confirmed insects as an excellent source of several vitamins and minerals including iron, potassium, calcium and magnesium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insects have been proposed as an efficient and high-quality alternative protein source for poultry [ 37 , 38 ], swine [ 11 , 39 ] and carnivorous fish [ 13 , 15 , 16 , 17 , 20 , 40 ] and interest in use of insect meals in perch diets is high. Insects are a viable source of protein and lipids [ 9 , 10 ] and a typical component of Eurasian perch natural diet. Nogales-Mérida [ 9 ], confirmed insects as an excellent source of several vitamins and minerals including iron, potassium, calcium and magnesium.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interest has turned to PAPs from insects as a component of aquafeeds [ 9 , 10 ]. Insect larva meals are rich in proteins and their EAA profile is close to that of FM and considered superior to that of plant proteins [ 9 ]. The use of insect PAP has recently been sanctioned by the European Commission (Brussels, Belgium) (Regulation 2017/893/EC, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…; Nogales‐Mérida et al . ). As human food, insects are considered as a healthy and nutritious food and, although entomophagy is not common in Europe and western world, insects have served in the food needs of other cultures for centuries (Anankware et al .…”
Section: Utilization As a Food And Feed Sourcementioning
confidence: 97%
“…The interest of using insects in animal feed is increasing [35,36], and inclusion of BSFL have been investigated in diets for pigs [9], chicken [12] and sh [11,37], but to this date, there is limited information about the effect of high dietary inclusion levels. The present study demonstrated that up to 19.06% fullfat BSFL meal can be included as an alternative protein and energy source in pelleted diets for weaned piglets without affecting growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…Ingredients, g/kg as fed Control BSFL5 BSFL10 BSFL20 The farm had an ongoing issue with edema disease and symptoms resulted in antibiotic treatment of ve pigs on days 8-10 PW. After one pig died without any registered symptoms on day 11 PW, all pigs were treated with intramuscular antibiotic injections (Borgal vet., Ceva Santé Animale, France) for three consecutive days (11)(12)(13). After treatment, all pigs appeared healthy throughout the experiment.…”
Section: Dietary Treatmentsmentioning
confidence: 99%